(untitled) (Italian Journal of Public Health, 2012)
If animals may be a source of hazards for humans, the reverse is equally true. The main sources of hazards from humans to animals, are the impact of human introduction of transboundary animal diseases, climate change, globalisation, introduction of invasive species and reduction of biodiversity.There is also a trend toward reducing genetic diversity in domestic animals, such as cattle; there are presently around 700 different breeds of cattle many of which at the verge of extinction (less than 100 reproductive females). The impact of humans is also indirect through detrimental effects on the environment. It is therefore urgent to implement the new concept of “one health"....